Bahasa al-Qur’an: Antara Doktrin Kebenaran Agama dan Kaidah Kebahasaan - Djamaluddin, Burhan; Nurlailah, Nurlailah; Zamzamy, Ahmad (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2026)
This study aims to examine the relationship between Arabic linguistic rules and certain Qur’anic expressions that appear not to fully conform to established norms of nahwu and imlāʾ. Employing a qualitative approach with a descriptive-interpretative method, this research analyzes various forms of perceived linguistic irregularities and the interpretive strategies developed by classical and contemporary scholars to account for them. The findings indicate that such apparent inconsistencies are not considered errors; rather, they are understood as part of the distinctive uslūb (stylistic features) of the Qur’an, encompassing rhetorical, eloquent (balāghah), and inimitable (iʿjāz) dimensions. Consequently, interpretive efforts seek to reconstruct linguistic understanding in a way that remains consistent with the belief in the Qur’an’s absolute truth. This study underscores that a linguistic approach to the Qur’an requires an epistemological framework that goes beyond normative grammatical rules, incorporating theological and rhetorical dimensions inherent in the text.